2019
DOI: 10.1002/ptr.6556
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Ganoderic Acid A exerts the cytoprotection against hypoxia‐triggered impairment in PC12 cells via elevating microRNA‐153

Abstract: Ganoderic Acid A (GAA) is often applied for healing cardiovascular and cerebrovascular ailments, but the influences in cerebral ischemia injury are still hazy. The research delved into the functions of GAA in hypoxia‐triggered impairment in PC12 cells. PC12 cells received hypoxia management for 12 hr, and subsequently, cell viability, migration, apoptosis, and correlative protein levels were assessed. After preprocessing with GAA, above cell behaviors were monitored again. The vector of microRNA (miR)‐153 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Triterpenoids produced by G. lucidum have a variety of biological properties, including antioxidant, antimicrobial, antitumor, anti-hepatitis B, and anti-HIV-1 activity [ 33 ]. Their high concentration in G. lucidum influences its pharmacological properties, including antiaging, anti-inflammatory, immunomodulatory, and antitumor properties [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Triterpenoids produced by G. lucidum have a variety of biological properties, including antioxidant, antimicrobial, antitumor, anti-hepatitis B, and anti-HIV-1 activity [ 33 ]. Their high concentration in G. lucidum influences its pharmacological properties, including antiaging, anti-inflammatory, immunomodulatory, and antitumor properties [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wan et al found that GAA can alleviate LPS-induced lung tissue damage [ 25 ]. Li et al noted that GAA may ameliorate hypoxia-induced PC12 cell damage [ 26 ]. Therefore, it is suggested that GAA has the function of treating FD symptoms and has the potential to become a drug for the treatment of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderic acid A can improve renal fibrosis and relieve renal dysfunction by inhibiting the over-activation of TGF-β/Smad signal, the expression of fibronectin and the deposition of extracellular matrix (ECM) in kidney ( Geng et al, 2020 ). Ganoderic acid A activates PI3K/AKT and mTOR by up-regulating miR-153, thereby improves the symptoms of cerebral hypoxia, provides a scheme for the treatment of cardiovascular and cerebrovascular diseases ( Li et al, 2020 ). It also inhibits the release of histamine from cells and promotes the digestion of various organs of the digestive system ( Lei, 2019 ).…”
Section: Pharmacological Activities Of Ganoderic Acidsmentioning
confidence: 99%